A Study Of Students Motivation And Risk-Taking In Learning Speaking At English Education Study Program Of Muhammadiyah University Of Bengkulu - Hendri Widodo; Dian Susyla; Epi Wadison (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The title of this research is A Study of Students’ Motivation and Risk-Taking in Learning Speaking at English Education Study Program of Muhammadiyah University of Bengkulu. The objective of this research was the students’ motivation and risk-taking in learning speaking at fifth semester English students in Academic Years 2016/2017 at Muhammadiyah University of Bengkulu and the limited on the research only focus on learning speaking. The design of the research was descriptive research. This method used to get the description by analyzing, interpreting and concluding. In the case, the researcher wanted to find out about the type students’ motivation and risk-taking in the fifth semester. In collecting the data, the researcher met the students in the fifth semester inside and outside of the class. Then the researcher gave the questionnaire. Next, ask the students to answer the questionnaire. After that the researcher took back the questionnaire and accumulated it to reinforce the result of this research. After that the researcher analyzed the data, so the researcher concluded that the type of students’ motivation and risk-taking of fifth semester was extrinsic motivation (62.2%) and analytical risk-taking (60.6%). The researcher suggested that the students to learning speaking more seriously and use the spend time to practice and study. The result of this research could be as a reference for the next researcher. Key word : Motivation, Risk-Taking